Genetically predicted hypertension, antihypertensive drugs, and risk of erectile dysfunction: a Mendelian randomization study - Zhao, Cong; Feng, Jun-long; Deng, Sheng; Wang, Xiang-peng; Fu, Yu-jie; Wang, Bin; Li, Hai-song; Meng, Fan-chao; Wang, Ji-sheng; Wang, Xian (Frontiers in Cardiovascular Medicine, 2023)
Genetically predicted hypertension, antihypertensive drugs, and risk of erectile dysfunction: a Mendelian randomization study